Analysis of U87 glioma cells by dielectrophoresis. Issue 12 (26th April 2022) - Sengul, Esra; Sharbati, Pouya; Elitas, Meltem; Islam, Monsur; Korvink, Jan G.
Abstract: Glioblastoma multiforme is the most aggressive and invasive brain cancer consisting of genetically and phenotypically altering glial cells. It has massive heterogeneity due to its highly complex and dynamic microenvironment. Here, electrophysiological properties of U87 human glioma cell line were measured based on a dielectrophoresis phenomenon to quantify the population heterogeneity of glioma cells. Dielectrophoretic forces were generated using a gold‐microelectrode array within a microfluidic channel when 3 Vpp and 100, 200, 300, 400, 500 kHz, 1, 2, 5, and 10 MHz frequencies were applied. We analyzed the dielectrophoretic behavior of 500 glioma cells, and revealed that the crossover frequency of glioma cells was around 140 kHz. A quantifying dielectrophoretic movement of the glioma cells exhibited three distinct glioma subpopulations: 50% of the glioma cells experienced strong, 30% of the cells were spread in the microchannel by moderate, and the rest of the cells experienced very weak positive dielectrophoretic forces. Our results demonstrated the dielectrophoretic spectra of U87 glioma cell line. Dielectrophoretic responses of glioma cells linked population heterogeneity to membrane properties of glioma cells rather than their size distribution in the population.